Cultural Awareness: Nursing Care of Iraqi Patients. (September 2015) - Goodman, Petra; Edge, Bethany; Agazio, Janice; Prue-Owens, Kathy
Purpose: The aim of this study was to describe the cultural factors that have an impact on military nursing care for Iraqi patients. The results were part of a larger study in which the purpose was to understand nurses' experiences of delivery of care for Iraqi patients.Method: Three focus groups, consisting of military registered nurses and licensed practical nurses, were used to generate rich descriptions of experiences in a military combat support hospital in Iraq. Data were analyzed using thematic analysis methods.Findings: Culturally, the differences between the Iraqi patients and the nurses included variations in communication, diet, and beliefs and values in reference to gender and patient dependency.Conclusion: The findings indicated that the nurses need language skills and cultural customs and beliefs training to provide care to culturally diverse patients. In addition, support services, such as dieticians, need to be involved in the plan of care to address applicable cultural issues.Implications: Implementation of learning to provide nurses language skills and cultural awareness of the diet, customs and beliefs of Iraqi people as well as the economic, political, and social factors that have an impact on their lives will promote quality nursing care and optimal health outcomes.